2021
DOI: 10.1097/pec.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Utilization of FilmArray Meningitis/Encephalitis in Children With Suspected Central Nervous System Infection

Abstract: Background:The etiology of central nervous system infections is often difficult to establish. FilmArray meningitis/encephalitis (ME) panel is a multiplex polymerase chain reaction for rapid identification of 14 pathogens. The aim of this study was to evaluate potential real-life contributions of the use of this method in the pediatric population. Methods:We herein report the results obtained with FilmArray ME in a retrospective case series of 367 children with suspected central nervous system infection. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Similar to our results, Messacar et al 19 demonstrated reduced acyclovir treatment and treatment duration for HSV-positive patients by FAME compared with positive HSV results by single-plex PCR. Barros Domingues et al 8 evaluated 367 FAME that were positive with identification of virus (viral infection) in 186 (50.7%) and positive with identification of a bacterial agent (bacterial infection) in 12 (3.3%). The most common viral pathogen was Enterovirus spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our results, Messacar et al 19 demonstrated reduced acyclovir treatment and treatment duration for HSV-positive patients by FAME compared with positive HSV results by single-plex PCR. Barros Domingues et al 8 evaluated 367 FAME that were positive with identification of virus (viral infection) in 186 (50.7%) and positive with identification of a bacterial agent (bacterial infection) in 12 (3.3%). The most common viral pathogen was Enterovirus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies evaluated FAME performance in the diagnosis and the effects on treatment duration, hospital stay, and hospital costs. 8 10 11 12 13 14 Therefore, we aimed to compare the performance of FAME, a molecular diagnostic method, in children with suspected ABM to traditional microbiological diagnostic methods such as cell counts and differentials, glucose and protein concentrations, microscopy, Gram staining, and bacterial culture from a CSF sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation